SPEECH FUNCTION OF MALE AND FEMALE TEACHERS IN CLASSROOM INTERACTION - Pohan, Febri Yanti Nurkhalizah; Husein, Rahmad; Ginting, Siti Aisah (TRANSFORM: Journal of English Language Teaching and Learning, 2019)
The research dealt with speech function used by male and female teachers in classroom interaction. The aims of this study were: (1) to discover the types of speech function used by male and female teachers in classroom interaction (2) to describe how the speech functions are realized as the ways they are (3) to elaborate the reasons why the speech function are realized as the ways they are. This study used descriptive qualitative design. The data were collected by following instruments: observing, recording and interviewing. The finding of this study revealed that: (1) the types of speech function that have been found in the male and female teachers in the classroom are statement, question, offer, command, initiating minor, acknowledgement, contradiction, answer, compliance and responding minor. (2) For the realization of speech function by male male and female teachers, there are two ways that have been found in realization of mood structure of male and female teachers talk, namely, typical clause mood, and non typical clause mood. In typical clause mood, there are four ways that have been found, namely statement that realized in declarative mood, then, question that realized in interrogative mood, command that realized in imperative mood, after that minor initiating that realized in minor. Beside that, in non typical clause mood, it is found there are four ways in realization of mood by male and female teachers, namely statement that realized by tagged declarative, question that realized by declarative, offer that realized by declarative and command that realized by declarative.(3) For the reasons in realization of mood by male and female teachers, In this study, the researcher found that reasons in realization of speech function of male and female teachers during the learning process was affected by teachers™ belief related to the teacher™s knowledge about the mood which are typical mood (congruent) and non-typical mood (incongruent). In typical mood, male and female teachers believe by initiating statement, initiating question, and initiating command have particular reasons. In non-typical mood (incongruent), both of male and female teachers believe that the use of Indonesian language influences the realization of speech function in metaphorical remarkKeywords: Speech Functions, Gender and Classroom Interaction.